Gelatinization Behavior, Morphological, and Chemical Properties of Flour of Cassava, Sago, and Wheat - Setya Budi Muhammad Abduh; Nurwantoro; Sri Mulyani; Arif Rizqi Nurwidiyanto; Sri Hestiningsih Widiyanti (ASEAN Journal of Chemical Engineering, 2024)
Gelatinization is an important property tailoring the functionalities of starch present in flour. This study aimed to investigate the gelatinization properties of Indonesian cassava and sago flours, namely tapioca, modified cassava flour, modified cassava starch, sago starch, and from soft and hard wheat. The gelatinization properties were investigated based on pasting and thermal properties, which were analyzed by means of a rapid visco analyzer (RVA) and differential scanning calorimetry (DSC), respectively. In addition, the morphological property was investigated using polarized microscopy, and chemical properties, namely solid, protein, lipid, ash, and crude fiber, were analyzed respectively using thermogravimetry, Kjeldahl, solvent extraction, and acid hydrolysis. It is found that flours of cassava, wheat and sago show pasting temperature (°C) of 69 – 71, 83 – 85, and 74; peak viscosity (cp) of 5400 – 5800, 2400 – 2700, and 2065; breakdown viscosity (cp) of 2600 – 4000, 900 – 1200, and 1493, setback viscosity (cp) of 1000 – 1500, 1000 – 1100, and 1063, final viscosity (cp) of 2800 – 3100, 2500 – 2700, and 1635. For gelatinization temperature (°C), they show onset temperature of 66 – 69, 54 – 60, and 72.04; peak temperature of 70 – 74, 60 – 64, and 75.93; conclusion temperature of 78 – 81, 66 – 69, and 80.99; and enthalpy change (J/g) of 8 – 12, 3 – 6, and 9.78. It can be concluded that flour and starch of cassava show the highest pasting profile (temperature and viscosity), while sago shows the lowest among the samples. Sago shows the highest gelatinization temperatures but the lowest enthalpy among samples. Starches of cassava show a round granular shape, smaller than wheat, while sago shows an oval shape. Considering the chemical composition, higher protein leads to higher pasting temperatures, and higher amylopectin content leads to higher peak and breakdown viscosities that might influence the gelatinization properties of flours.